Polarization-Insensitive Silicon Photonic Variable Optical Attenuator - Meixin Li; Yuxuan Zhang; Hao Jiang; Haoran Wang; Danni Luo; Jing Yang; Yabin Li; Zanyun Zhang (Photonics)
We propose and demonstrate a polarization-insensitive silicon photonic variable optical attenuator. The designed device uses a two-dimensional apodized grating coupler as a surface-normal coupling interface, which has the advantages of low-cost fiber packaging and polarization insensitivity. For optical attenuation, PIN diodes are inserted into each waveguide to act as optical absorbers. The compact device, featuring a footprint of 250 × 850 μm2, exhibits a fiber-to-fiber insertion loss of 6 dB. Under a 3 V bias voltage, wavelength-dependent attenuation of 18 dB at 1295 nm and 26 dB at 1315 nm is achieved. Systematic characterization across diverse input polarization states confirms polarization-dependent loss below 0.5 dB under arbitrary polarization states, validating the device’s robust polarization insensitivity for wavelength-division multiplexing systems.